Air - Duffy, Cian (Romanticism on the Net, 2023)
This essay takes those exhibits in RÊVE (Romantic Europe: The Virtual Exhibition) that are connected to “air” as points of departure for a survey of the renewed interest in air in Romantic-period cultural texts from across Europe. Scholarly interest in Romantic air has burgeoned of late but has often tended to prioritise metaphorical senses of the term or cognate terms such as atmosphere. This essay, conversely, focuses on more literal engagements with what Percy Shelley, in Prometheus Unbound, calls the “all-sustaining air.” Beyond this primary focus on the literal, however, the essay is also attentive to overlap between actual and metaphorical air in the specific context of the (Romantic) museum, with its complex evocation of what we might call “the air of the past,” an evocation which many of the Romantic-period texts considered here anticipate.